IELTS target 5.0 leading to IELTS acadmic : - Gough, Chris (Tổng hợp Thành phố Hồ Chí Minh, 2010)
This book consists of 15 unit, each unit consists 5 modules: speaking and vocabulary, listening, reading, writing